Reakcii anticipacii v bokse i dzjudo - Akopyan, A. O.; Kulagina, L. A.; Telyuk, S. I. (Vestnik sportivnoj nauki; Sports science bulletin, 2018)
The article presents the results of studies of reactions of anticipations in high-class athletes in judo (men) and boxing (women). A technique for studying the specific motor memory of athletes and the conditions for the formation of reactions of anticipation is presented. The questions of the stability of reactions of anticipation to the confounding factors of physical loads of the training process and competitive fights are considered.